EFEKTIVITAS KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA DENGAN KEPUASAN KERJA GURU MADRASAH ALIYAH SWASTA DI KOTA SUKABUMI - Isman Kadar (Universitas Pakuan, 2014)
Research on the Effectiveness of Interpersonal Communication and Work Motivation with Teacher Job Satisfaction aims to examine the relationship between two independent variables, namely the Effectiveness of Interpersonal Communication (X1) and Work Motivation (X2), the dependent variable is Teacher Job Satisfaction (Y). The population of this research is all Private School of Madrasah Aliyah teachers who were civil servants in the district Sukabumi. The samples in this study were drawn from a population of 104 teachers. There is a positive and highly significant relationship between the Effectiveness of Interpersonal Communication and Work Motivation working together with Teacher Job Satisfaction with the regression equation ? = 22,565 + 0,414X1 + 0,359X2.Keywords: Effectiveness of Interpersonal Communication , Work Motivation, Teacher Job Satisfaction